Value-Based Administration Services and Value-Based Care: Aligning Administrative Efficiency with Patient Outcomes - Michael Mncedisi Willie (University of Science and Computer Technology, 2025)
Value-Based Care (VBC) is reshaping healthcare delivery by incentivising improved patient outcomes over service volume. However, its success is closely tied to the efficiency and responsiveness of administrative systems.This study introduces the concept of Value-Based Administration Services (VBAS) and explores how its integration with VBC can strengthen clinical performance, enhance operational efficiency, and support organisational sustainability. A qualitative literature review was conducted to analyse peer-reviewed articles, policy documents, and case studies. Thematic analysis was used to identify patterns and construct a conceptual framework illustrating the interdependence of VBAS and VBC. Findings indicate that administrative functions such as claims processing, fraud detection, and performance-based contracting are essential to achieving VBC objectives. Misaligned or inefficient administrative processes can compromise patient care, while well-structured VBAS systems support transparency, regulatory compliance, and cost control. VBAS enables VBC, transforming administrative functions from transactional support roles into strategic mechanisms for delivering value. The proposed framework offers healthcare leaders a practical model for aligning administrative and clinical strategies to achieve high-quality, patient-centred, and financially sustainable care.